PERKEMBANGAN TELEMEDIS SEBAGAI PENDUKUNG PELAYANAN KESEHATAN: TELAAH PUSTAKA - Daniel C.A. Nugroho (Berkala Ilmiah Kedokteran Duta Wacana, 2019)
Telemedicine is a method in health service using information technology and telecommunication for helping promotive, preventive, curative and rehabilitative act. The initial media used for this method are telegram or telephone. Telemedicine was growing rapidly after the internet, by e-mail, or internet-based message services. Various problems on health services such as costs, distance, time constraint, efficiency, and the necessity of continuous patient monitoring are the reasons why telemedicine need to be discussed further. Telemedicine methods have many shortcomings. Therefore, this review would explain several types of telemedicine as well as its advantages and disadvantages.